Modelling complex molecular interactions in catalytic materials for energy storage and conversion in nuclear magnetic resonance - Hu, Wenda; Jaegers, Nicholas R.; Winkelman, Austin D.; Murali, Shiva; Mueller, Karl T.; Wang, Yong; Hu, Jian Zhi (Frontiers in Catalysis, 2022)
Nuclear magnetic resonance (NMR) is a non-destructive and atom-specific specific tool that has become a burgeoning analytic method for understanding the detailed molecular interactions in catalysis and energy storage materials. However, the observation of diverse chemical shifts arising from complex molecular interactions makes the interpretation of NMR spectroscopy increasingly challenging, in particular for a novel system without standards for comparison. Density functional theory-NMR (DFT-NMR) is an indispensable tool to mitigate these challenges and provide detailed 3D molecular structures that relate materials and reaction intermediate structures, and information about chemical interactions, dynamics, and reaction mechanisms. This review provides a fundamental background in DFT-NMR relating to theory development, critical parameters for calculating NMR properties, computational accuracy, and the current capabilities. A variety of practical examples from the fields of catalysis and energy storage are summarized to illustrate the capabilities of DFT-NMR application to date. Last but not least, cautionary notes on the application of these strategies are presented for researchers modeling their own systems.